-2•[3-(6)²:(-9)]-2•[5-(-7)]= ....
Răspunsuri la întrebare
Răspuns de
1
Răspuns:
-2•[3-(6)²:(-9)]-2•[5-(-7)]=
-2•[3-(2×3)²:(-3²)]-2•(5+7)=
-2[3-4(-1)]-2×12=-2(3+4)-24=-14-24=-38
Răspuns de
0
-2•[3-36:(-9)]-2•12=
-2•(3+4)-24=
-14-24=
-38
-2•(3+4)-24=
-14-24=
-38
Alte întrebări interesante
Informatică,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
9 ani în urmă
Ed. muzicală,
9 ani în urmă
Limba română,
9 ani în urmă